Remote neuropsychological assessment: Acceptability and feasibility of direct-to-home teleneuropsychology methodology during the COVID-19 pandemic. Issue 2 (17th February 2023) - Sumpter, Ruth; Camsey, Emma; Meldrum, Steven; Alford, Max; Campbell, Iain; Bois, Catherine; O'Connell, Susan; Flood, John
Abstract: Objective: To determine the acceptability and feasibility of telephone and video-conference calls to complete cognitive assessments during the COVID-19 pandemic. Method: In rapid response to the pandemic, evidence-based adaptations were made to routine face-to-face (FTF) practice, delivering teleneuropsychology (TNP) within a National Health Service (NHS) Scotland neuropsychology service. Caldicott guardian approval was obtained to complete a six month study (April to October 2020) from the early stages of the first United Kingdom (UK) lockdown. Assessments were completed with patients in their own homes (direct-to-home) via remote connections. Neuropsychology clinicians, service-users and referring agents were approached for structured feedback and qualitative comment. Results: Data was captured for 212 referrals assessed by seven clinical psychologists; with responses from 70 (33%) service-users and 14 (58%) referring agents. 94% of referrals were assessed remotely and discharged. TNP reduced defaulted appointment discharge rates. Gender, socioeconomic deprivation and age did not affect access to information technology (IT) equipment. Clinicians agreed that remote assessment allowed them to complete initial interview (96%) and formulate (77%) cases appropriately. Service-users agreed they were comfortable with equipment (84%), the process was straightforward (74%), and would recommend TNP to others (68%). Referring agents were satisfied with the service provided (100%). Limitations included evidence-based remote test availability, technical issues and home distractions. Conclusions: Study findings evidence the acceptability and efficiency of TNP; increasing service accessibility, while reducing infection risk, defaulted appointments and travel. The results advocate for a post-pandemic mixed model of service delivery encompassing both FTF and TNP approaches.